2015
DOI: 10.1111/eos.12232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a functional monomer (MDP) on the enamel bond durability of single‐step self‐etch adhesives

Abstract: The present study aimed to determine the effect of the functional monomer, 10-methacryloxydecyl dihydrogen phosphate (MDP), on the enamel bond durability of single-step self-etch adhesives through integrating fatigue testing and long-term water storage. An MDP-containing self-etch adhesive, Clearfil Bond SE ONE (SE), and an experimental adhesive, MDP-free (MF), which comprised the same ingredients as SE apart from MDP, were used. Shear bond strength (SBS) and shear fatigue strength (SFS) were measured with or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 30 publications
1
33
0
1
Order By: Relevance
“…Bond-strength testing comparing MDP-free with MDPcontaining adhesives showed nevertheless that chemical interaction of MDP with HAp, while perhaps less relevant at short time, is crucial in maintaining interfacial stability over time. Very recent research confirmed this even in case an E&R approach is employed (Tsuchiya et al, 2016).…”
Section: Discussionmentioning
confidence: 84%
“…Bond-strength testing comparing MDP-free with MDPcontaining adhesives showed nevertheless that chemical interaction of MDP with HAp, while perhaps less relevant at short time, is crucial in maintaining interfacial stability over time. Very recent research confirmed this even in case an E&R approach is employed (Tsuchiya et al, 2016).…”
Section: Discussionmentioning
confidence: 84%
“…Specimens were made and stored as described above for SBS testing, and 30 specimens were used for each test condition. The staircase method of fatigue testing reported by Draughn was used for SFS testing, as previously reported . The initial maximum load for SFS testing was set to 50–60% of the SBS determined for that adhesive system, and the minimum load was maintained closed to zero (0.4 N).…”
Section: Methodsmentioning
confidence: 99%
“…It has been asserted that the quality of chemical bonding with MDP monomer might be time-dependent. Bonding agents containing MDP have been proven to form nanolayering structures that appear very stable according to their low dissolution rate in water [22]. …”
Section: Discussionmentioning
confidence: 99%